Project for a better attention to immigrant population in primary health in Catalonia - Maria Rosa Rifà Ros; Lluís Costa Tutusaus; Cristina Olivé Adrados; Ángela Pallarés Martí; Isabel Pérez Pérez; Carmen Vila Gimeno (Universidad de Alicante, 2012)
The present research study tries to apply the nursing methodology of NANDA, NOC and NIC taxonomy to an immigrant population and presents the following Aims: - To identify the most prevalent NANDA diagnoses linked to the migratory process of immigrant population and their families. - To elaborate and implement nursing care schemes adequate to the immigrant population and their families, using NANDA, NOC and NIC taxonomy. - To evaluate suitability and validity of the already made standard schemes. Methodology: The project is being dealt with in several Primary Health Centres of the Institut Català de la Salut (ICS) in Catalonia previously selected. The multi-centre study has four stages: a) A descriptive stage: Detection of needs in the immigrant population by 60 nurses responsible for the data collection. b) Preparing some standard care plans according to the detected problems using the appropriate nursing language. c) Implementing those standard care plans. d) Outcomes measure and assessment. Conclusions: Innovative elements as methodological triangulation are here presented in order to show the small scientific nursing evidence. 47 diagnoses associated to those factors and definite characteristics have been identified.